Prevention starts from the crib: the pediatric point of view on detection of families at high cardiovascular risk - Maria Elena Capra; Cristina Pederiva; Giuseppe Banderali; Giacomo Biasucci (BMC, 2021)
Abstract Background Cardiovascular disease (CVD) is one of the main causes of mortality and morbidity in Italy. Hypercholesterolemia is a modifiable CVD risk factor. The detection and treatment of hypercholesterolemia can modify the natural history of CVD, making CVD risk for affected patients comparable to that of unaffected ones. In this scenario, the detection of families at high cardiovascular risk is the first step of CVD prevention. This multicenter, observational study is aimed at finding an effective and non-invasive screening strategy to detect families at high risk for CVD. Methods A survey investigating the knowledge of lipid and CVD issues was distributed to the parents of all infants born at the Neonatology Unit of Piacenza City Hospital and San Paolo Hospital in Milan over a 6 months period. Overall, 554 surveys have been collected. Results 26.8% newborns had parents who knew their own lipid profile, 40.2% had parents who knew the correct normal blood values of total cholesterol, 37.1% had parents who declared to have first or second degree relatives with lipid disorders, 33.7% had parents who declared to have first or second degree relatives with premature CVD Conclusion Collecting a problem-tailored and accurate family history seems to be a good strategy to detect high risk families. Our data suggest that the percentage of adults who are unaware of their lipid profile, with a positive family history for CVD and/or lipid disorders is higher than expected. As a result, even the number of undetected paediatric patients at high cardiovascular risk might be greater than expected.